Hubungan Rasio Neutrofil Limfosit (RNL) terhadap kejadian relaps pada anak dengan sindrom nefrotik di RSUP Sanglah, Bali, Indonesia - Wega Upendra Sindhughosa; Gusti Ayu Putu Nilawati; Ni Putu Siadi Purniti; Bagus Ngurah Putu Arhana; Ketut Ariawati; Putu Junara Putra (Intisari Sains Medis, 2020)
Background: Nephrotic Syndrome is a disease whose cause is not fully known and has a high relapse rate. The lymphocyte neutrophil ratio is a marker of inflammation in patients with malignancy, infection, and coronary heart disease. This study aims to determine the relationship between Neutrophil Lymphocyte Ratio (NLR) and the occurrence of relapse nephrotic syndrome.Methods: This study was a retrospective analytic observational study with a cross-sectional approach to finding the relationship between increased NLR and the incidence of relapse in patients with nephrotic syndrome at SMF Children's Health Sciences Faculty of Medicine Universitas Udayana/Sanglah General Hospital. Data were taken from medical records of 45 respondents with episodes of relapse or remission from January 2018-January 2019. Data were analyzed using SPSS version 20 for Windows.Results: The results showed that most of the subjects were male (71.1%), aged 1-5 years (51.2%), and aged 4.00 ± 8.50 years in both the relapse and remission groups. However, the infection rate (66.7%) and medication adherence (75.0%) tended to be higher in the relapse group. The analysis of the ROC curve shows the cut-off point of NLR was 2.36 (AUC: 0.521), with a sensitivity of 71.1% and a specificity of 73.3%. There was a significant relationship between the NLR value and the incidence of relapsed nephrotic syndrome in multivariate analysis (adjusted OR: 4.53; 95% CI: 1.68 - 12.22; p = 0.003).Conclusion: This study shows that there is a relationship between an increase in RNL and the incidence of relapse in pediatric nephrotic syndrome patients at Sanglah General Hospital, Bali, Indonesia. Latar belakang: Sindrom Nefrotik merupakan salah satu penyakit yang penyebabnya belum sepenuhnya diketahui dan memiliki angka relaps yang tinggi. rasio neutrofil limfosit merupakan suatu pertanda inflamasi pada pasien yang mengalami keganasan, infeksi dan penyakit jantung koroner. Penelitian ini bertujuan untuk mengetahui hubungan Rasio Neutrofil Limfosit (RNL) dengan terjadinya sindrom nefrotik relaps.Metode: Penelitian ini merupakan penelitian retrospektig observasional analitik dengan pendekatan potong lintang untuk mencari hubungan peningkatan RNL terhadap kejadian relaps pada pasien sindrom nefrotik di SMF Ilmu Kesehatan Anak FK UNUD/Rumah Sakit Umum Pusat Sanglah. Data diambil dari rekam medik terhadap 45 responden dengan episode relaps maupun remisi dari Januari 2018-Januari 2019. Data dianalisis dengan SPSS versi 20 untuk Windows.Hasil: Hasil penelitian menunjukkan bahwa sebagian besar subyek adalah laki-laki (71,1%), berusia 1-5 tahun (51,2%), maupun berusia 4,00±8,50 tahun baik pada kelompok relaps maupun remisi. Akan tetapi angka infeksi (66,7%) maupun ketidak patuhan pengobatan (75,0%) cenderung lebih tinggi pada kelompok relaps. Analisa kurva ROC menunjukkan titik potong RNL sebesar 2,36 (AUC: 0,521) dengan sensitivitas 71,1% dan spesifisitas 73,3%. Terdapat hubungan bermakna antara nilai RNL dengan kejadian sindrom nefrotik relaps pada analisis multivariat (adjusted OR: 4,53; 95%IK: 1,68 – 12,22; p=0,003).Simpulan: Penelitian ini menunjukkan bahwa terdapat hubungan antara peningkatan RNL terhadap kejadian relaps pada penderita sindrom nefrotik anak di RSUP Sanglah, Bali, Indonesia